Technology’s roles in student-centred learning in higher education - Trinidad, Jose Eos R (Archīum Ateneo, 2019)
Given challenges of covering course content, ensuring skills acquisition, and assessing student’s work, higher education faculty often experience difficulties in practicing student-centered learning. The education literature has shown that one way of addressing these concerns is through the use of educational technologies. In this action research, ten faculty members from a Philippine university participated in a coaching programme on using technology for student-centered learning. From interviews and classroom observations, the study finds that when introduced to appropriate tools, higher education faculty use technologies for interactive learning, timely feedback, and better engagement with students. The present research elaborates how faculty from different departments have used these technologies and how the students have responded to their use. The study contributes to the discussion of how technologies can enhance student learning and complement classroom instruction.